EFEKTIVITAS TEKNIK SELF TALK UNTUK MENINGKATKAN KESADARAN DIRI MAHASISWA PENGHAFAL AL-QUR’AN - Ade Amalia Khodijah; Wiantina, Nur Azmi; Muttaqin, Muhammad (Institut Daarul Qur'an Jakarta, Indonesia, 2024)
The study aims to produce group guidance on effective self talk techniques to increase self awareness of Qur’an memorization students, obtain student self awareness profiles, and find out the effectiveness of self talk techniques to increase self awareness of Qur’an memorization students at the Daarul Qur’an Institute. This research method uses experimental methods that are included in quantitative methods with a type of quasi exsperimental design in the form of pretest posttest nonequivalent control group design. The study population was 70 students. The sample technique used was purposive sampling and obtained 12 students who were divided into experimental groups and control groups. The data collection technique used was through questionnaires and interviews, then the data was analyzed using an independent sample t-test through the SPSS program version 25. The results of this study show that group guidance services with self talk techniques have an influence to help increase students self awareness. Based on the results of pretest and posttest hypothesis tests through independent sample t-test tests in the experimental group of 0.002, it states that 0.002 < 0.05 so that the self talk technique effective to increase self awareness of students memorizing the Qur’an. Keywords: Self Awareness; Self Talk; Qur’an Memorization.